Research on consumers’ intended usage of cold chain logistics service through fresh-food apps based on the structural equations model - Zhang, Mengze; Fabus, Michal; Zhang, Yizhou (Business: Theory and Practice, 2024)
By expanding the theory of planned behavior with Structural Equation Modeling, the objective of the study is to investigate consumer behaviors in the purchasing of fresh food through fresh-food apps and cold chain logistics services usage in Shanghai and Beijing, China. The results showed that the usefulness of the fresh-food apps has a positive impact on consumers’ attitudes to enjoying apps’ cold chain logistics services. However, the ease of use of apps has never had a positive impact on consumers’ attitudes towards enjoying cold chain logistics services. Furthermore, consumers’ attitudes, perceived behavioral control and subjective norm have a positive impact on their intention to use cold chain logistics services via fresh food apps. Findings confirmed that attitude plays a part of mediating role in usefulness and behavioral intention.